The Effect of Using the Guessing Game Method on Decriptive Text on the Second Grade Students of SMP Swasta Satria Dharma Perbaungan in Academic Year 2021/2022 - Windy Puspita, Yugi Diraga Prawiyata (CV. Pusdikra Mitra Jaya, 2023)
This study aims to determine the effect of the use of the Guessing Game method in learning Descriptive Text. This research was conducted by seventh grade students of Satria Dharma Perbaungan Private Junior High School. This research method used quantitative methods with a pre-test-post test research design. Sampling was carried out by dividing the group into 2 classes, namely the experimental class and the control class. measurement to collect data and written test tools t. The results of the data found the effect of handling is 1.67 The conclusion is that there is a good influence from the use of the guessing game method in learning descriptive text.